Myeloma bone disease - Maciej Zaucha, Jan (Contemporary Oncology/Współczesna Onkologia, 2001)
New insights in the pathophysiology of myeloma bone disease are discussed. Bone disease is the major manifestation of myeloma multiplex. The presence of myeloma cells disturbs the delicate balance between osteolysis and osteosynthesis. Myeloma cells stimulate osteolysis directly through the production of TRANCE/RANKL molecule, which physiologically activates osteoclasts and indirectly through the production of syndecan-1 (CD138), which inhibits osteprotegerin, which in turn acts as a decoy receptor for TRANCE/RANKL. Increased osteoclastic activity leads to release from the bone marrow matrix of several cytokines, which stimulate myloma cells growth. Biphosphonates decrease the incidence and severity of bone lesions, however they do not prolong overall survival.